1997
DOI: 10.1063/1.118395
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of two-dimensional photonic crystals with graphite structure

Abstract: We present a study of the transmission coefficients of two-dimensional photonic band gap materials consisting of dielectric cylinders in graphite arrangement. By the study of the attenuation versus slab thickness, we determine the most efficient graphite configuration. We show how uncoupled modes create opaque regions for plane waves propagating along the Γ-P direction and widen the gap originating from the existence of forbidden photonic bands. Our results demonstrate that graphite structure is a promising ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…While several experiments [10,11] have studied twodimensional photonic crystals with a honeycomb or triangular lattice, the emphasis has been on the frequency range where the band structure has a true gap, rather than on frequencies near the Dirac point. Recent experiments on electronic conduction near the Dirac point of graphene have shown that this singularity in the band structure offers a qualitatively new transport regime [12].…”
Section: Discussionmentioning
confidence: 99%
“…While several experiments [10,11] have studied twodimensional photonic crystals with a honeycomb or triangular lattice, the emphasis has been on the frequency range where the band structure has a true gap, rather than on frequencies near the Dirac point. Recent experiments on electronic conduction near the Dirac point of graphene have shown that this singularity in the band structure offers a qualitatively new transport regime [12].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding PhC physics, the Kagomé structure is practically neglected [11], in spite of its large gapto-midgap ratio. On the other hand, the honeycomb or graphite lattice PhC has already been investigated [12][13][14][15] to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] He also pointed out that the strength of the coupling between the outside waves and the internal field at the interface substantially modifies the transmission. 19 This method has been widely used in studying the PhCs with graphite structure 22 and the vanishing transmission due to symmetry. [23][24][25][26][27][28][29][30][31][32][33] But this method shows the field distribution as sum of all expanded series which is also equal to sum of all propagating waves displayed by the FDTD method.…”
Section: Introductionmentioning
confidence: 99%